Islamic Civilization and Science Representation in 1001 Inventions and the Library of Secrets: A Barthesian Semiotic Analysis - Achmad Fachmi (Jurnal El-Pustaka, 2025)
Research on the representation of Islamic scientific heritage in movies can be conducted through discourse analysis with Roland Barthes' semiotic approach. The movie '1001 Inventions and the Library of Secrets' is worthy of study because it contains meanings and messages that reflect the contribution of Islamic civilization to science. The purpose of this study is to identify the contribution of Islamic civilization to science presented in the movie. A qualitative approach is used in this study for the data analysis process using Roland Barthes' semiotics. This study examines the denotative, connotative, and myth meanings in each scene of the movie '1001 Inventions and the Library of Secrets' using Roland Barthes' semiotic approach. The results of the study indicate that there is a main goal or ideology in the meaning of the movie, namely the affirmation that in the Middle Ages, there was a civilization that made a major contribution to the development of modern science, namely Islamic civilization. In addition, this movie also forms a counter-narrative to the dominance of Eurocentric history in the discourse of education and science. Thus, this movie successfully represents the important contribution of Islamic civilization to the development of science through a well-structured storyline, symbols, themes, and script. This study contributes to strengthening the use of movie as an effective alternative learning medium in Islamic education, especially in reintroducing the contribution of Islamic civilization to science.